FC 058THE IMPORTANCE OF ADDRESSING MULTIPLE RISK MARKERS IN TYPE 2 DIABETES: RESULTS FROM THE LEADER AND SUSTAIN 6 TRIALS. (29th May 2021) - Zobel, Emilie; Von Scholten, Bernt Johan; Hansen, Tine; Persson, Frederik; Rasmussen, Søren; Wolthers, Benjamin; Rossing, Peter
Abstract: Background and Aims: The extent to which improvements in multiple risk markers affect outcomes in type 2 diabetes is unclear. Our aim was to investigate whether clinically relevant improvement in multiple risk markers confers lower risk of micro- and macrovascular disease in a contemporary type 2 diabetes population with cardiovascular disease or high risk for cardiovascular disease, independent of specific treatments. Method: Exploratory post-hoc analysis of the two cardiovascular outcome trials in patients with type 2 diabetes LEADER (NCT01179048; n=8638 with baseline and year 1 assessment of at least one of the parameters of interest; patients randomised to the glucagon like peptide-1 receptor agonist [GLP-1 RA] liraglutide or placebo [1:1]; median observation time: 3.8 years) and SUSTAIN 6 (NCT01720446; n=3040 with baseline and year 1 assessment of at least one of the parameters of interest; patients randomised to the GLP-1 RA semaglutide or placebo [1:1]; median observation time: 2.1 years). We pooled all participants, including the active (liraglutide/semaglutide) and placebo-treated groups. We categorised patients according to number of risk markers with a clinically relevant change 1 year after randomisation and investigated subsequent risk of major adverse cardiovascular events (MACE: cardiovascular death, nonfatal myocardial infarction and nonfatal stroke), expanded MACE (MACE plus coronary revascularisation and hospitalisation for heart failure or unstable angina pectoris), cardiovascular death or nephropathy (new onset of macroalbuminuria or doubling of the serum creatinine level and an estimated glomerular filtration rate [eGFR] ≤45 ml/min/1.73 m2, or the need for continuous renal-replacement therapy, or death from renal disease). We defined clinically relevant change as: body weight loss ≥5%, glycated haemoglobin reduction ≥1%, systolic blood pressure reduction ≥5 mmHg, low-density lipoprotein cholesterol reduction ≥0.5 mmol/L, eGFR reduction ≥0 ml/min/1.73m2 and urinary albumin-to-creatinine ratio reduction ≥30% of baseline value. Numbers of risk markers with change were classified as: none (group G0), 1 (G1), 2 (G2), 3 (G3) and ≥4 (G4). Cox regression analysed risk of each outcome and tested for trends; models were adjusted for continuous baseline levels of the risk markers and treatment group (liraglutide/semaglutide and placebo) and stratified by trial. Results: The Table contains baseline characteristics of patients in each risk marker group. Compared to patients with no risk-marker improvement, patients with 2, 3 or ≥4 improved risk markers had reduced risk of expanded MACE [hazard ratio (95% CI): 0.80 (0.67-0.96); 0.80 (0.66-0.97); 0.82 (0.66-1.02)], cardiovascular death [0.66 (0.45-0.96); 0.67 (0.45-0.99); 0.60 (0.38-0.94)] and nephropathy [(0.71 (0.52-0.97); 0.48 (0.34-0.68); 0.43 (0.29-0.65)] (Figure ). One improved risk marker conferred no risk reduction. The trend of decreased risk for each additional risk marker improvement was significant for expanded MACE (p=0.004), cardiovascular death (p=0.005) and nephropathy (p<0.0001). We observed a stepwise higher number of patients on GLP-1 RA treatment in the groups with 0, 1, 2, 3 or ≥4 risk marker improvements as follows: 30.5% in G0, 38.0% in G1, 48.8% in G2, 61.6% in G3 and 75.3% in G4. We observed similar results in separate analyses of the LEADER and SUSTAIN 6 trials. Conclusion: In patients with type 2 diabetes, improvements in two or more risk markers confer reduced risk of cardiovascular disease and nephropathy as compared with none or one improved risk marker, most notably for nephropathy. Our findings stress the importance of multifactorial intervention and underscore the benefit of pleiotropic antidiabetic treatments.